(untitled) (Anwer Khan Modern Medical College Journal, 2011)
Friedewald’s formula is the most frequently used formula for the calculation of serum lowdensity lipoprotein cholesterol from serum total cholesterol, serum triacylglycerol and serum high-density lipoprotein cholesterol. Most laboratories use serum triacylglycerol concentration of 400 mg/dl as upper cut-off limit for the calculation of LDL cholesterol, but a combination of serum triacylglycerol to total cholesterol ratio and serum triacylglycerol may have more advantages than serum triacylglycerol concentration alone to use Friedewald’s formula effectively. The aim of this study was to determine the upper cut-off limit of serum triacylglycerol concentration and serum triacylglycerol to total cholesterol ratio to calculate LDL cholesterol using Friedewald’s formula in Bangladeshi population. Serum total cholesterol, serum triacylglycerol, serum high-density lipoprotein cholesterol and serum lowdensity lipoprotein cholesterol were measured by direct method on 644 sera obtained from adult Bangladeshi study subjects after 12 hours of fasting. Serum low-density lipoprotein cholesterol was also calculated by using Friedewald formula. Low-density lipoprotein cholesterol obtained by Friedewald’s formula in this study was compared with that obtained by direct method in different level of triacylglycerol and also in different triacylglycerol to total cholesterol ratio. Friedewald’s formula underestimates low-density lipoprotein cholesterol when serum triacylglycerol concentration >300 mg/dL. But when direct serum low-density lipoprotein cholesterol was compared with low-density lipoprotein cholesterol calculated using Friedewald’s formula up to serum triacylglycerol to total cholesterol ratio of 2, underestimation subsides, and the serum triacylglycerol level up to 700 mg/dl could be confidently included for the calculation of low-density lipoprotein cholesterol by Friedewald’s formula. Friedewald’s calculation formula can be confidently used up to serum triacylglycerol concentration of 700 mg/dl in Bangladeshi population, provided the serum triacylglycerol to total cholesterol ratio is two or less. Key Words: Friedewald Formula; Low-Density Lipoprotein Cholesterol